Strategi Lobi dan Negosiasi Dalam Membangun Kepercayaan Sponsorship Studi Kasus : Produk Hydro Coco - Lailani Octavia Rahmadhani; Kesya Melika; Alief Rahman Juliansyah; Ahmadhio Annuri Pratama; Lilik Sumarni (Populer: Jurnal Penelitian Mahasiswa, 2024)
This research examines the lobbying and negotiation strategies in building trust in Hydro Coco's sponsorship as an isotonic drink. The method used is descriptive qualitative with literature study approach. The findings showed that Hydro Coco implemented marketing strategies through proper segmentation, targeting, and positioning. The performance strategy was applied by sending creative proposals to the event organizers, while negotiations focused on unveiling the logo and product sections at the event. Hydro Coco also used various promotional tactics such as offering free samples, product bonuses, price discounts, personal selling, and direct marketing. This study concludes that effective lobbying and negotiation strategies can increase sponsorship trust and increase consumer loyalty to Hydro Coco products.